2002
DOI: 10.1034/j.1600-0544.2002.02203.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and genetic study of 121 cases of oral clefts in Kuwait

Abstract: No definite association was observed between consanguinity and the occurrence of facial clefts in Kuwait. General transmission models in the full data set showed no evidence of heterogeneity in the results between the Arab and nomad subsets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 24 publications
5
16
1
Order By: Relevance
“…CP occurred infrequently (8.5%) compared to other OFC. The results are consistent with most of previous studies [Gregg et al, 1980; Al‐Bustan et al, 2002; Baek et al, 2002; Suleiman et al, 2005]. The usual ratio of non‐associated CLP and CP is about 2–2.5:1 [Czeizel and Tusnadi, 1971; Tolarova and Cervenka, 1998; Hashmi et al, 2005].…”
Section: Discussionsupporting
confidence: 92%
“…CP occurred infrequently (8.5%) compared to other OFC. The results are consistent with most of previous studies [Gregg et al, 1980; Al‐Bustan et al, 2002; Baek et al, 2002; Suleiman et al, 2005]. The usual ratio of non‐associated CLP and CP is about 2–2.5:1 [Czeizel and Tusnadi, 1971; Tolarova and Cervenka, 1998; Hashmi et al, 2005].…”
Section: Discussionsupporting
confidence: 92%
“…Consanguineous marriages are an important factor in the development of cleft anomalies, as well as a host of other genetic abnormalities, and should be discouraged 20. Al-Bustan et al21 evaluated epidemiological factors such as gender and consanguinity that may be associated with cleft lip or cleft palate in Kuwait and found no definite association between consanguinity and the occurrence of facial clefts, but our study showed a statistically significant association between consanguinity and occurrence of craniofacial anomalies.…”
Section: Discussioncontrasting
confidence: 61%
“…Al-Awadi et al (1986) reported that prenatal and neonatal losses among consanguineous couples are higher than among non-consanguineous couples. For the occurrence of oral clefts, however, Al-Bustan et al (2002) showed that there is no definite association with consanguineous marriage.…”
Section: Introductionmentioning
confidence: 93%